Evaluation of the Performance Assessment System for Islamic School Principals: Challenges and Opportunities in Achieving Quality-Based Education - Muh. Nur Fithri Dahlan; Nurqadriani Nurqadriani; Muh. Nur Ridho Chaerul Firdaus (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study evaluated the implementation of the Performance Assessment for Islamic School Principals using the CIPP approach (Context, Input, Process, Product) to assess the relevance of its objectives, the adequacy of inputs, the effectiveness of processes, and its impact on the quality of education in Islamic schools. Method: Data were collected through in-depth interviews with principals and supervisors and direct observations in several Islamic schools. Results: The results indicated that the objectives of the Performance Assessment for Islamic School Principals aligned with the needs of Islamic schools in improving educational quality. However, challenges existed in the form of supervisor competencies and limited technological infrastructure, affecting the effectiveness of implementing the Performance Assessment for Islamic School Principals. The implementation process followed established procedures but still faced technical and administrative obstacles. The impact of Performance Assessment for Islamic School Principals on improving education quality was significant, particularly in strengthening management and enhancing teacher competencies. Novelty: The study recommended aligning Performance Assessment for Islamic School Principals indicators with local needs, improving training for supervisors, developing technological infrastructure, digitizing Performance Assessment for Islamic School Principals processes, and strengthening follow-up measures post Performance Assessment for Islamic School Principals through training and mentoring programs for principals. These findings highlighted the importance of a holistic and adaptive approach in implementing Performance Assessments for Islamic School Principals to achieve sustainable improvements in the quality of education in Islamic schools.